Bibliometric Analysis of Technology Trends in Education: Analysis from 2018 to 2022 - Wicaksono, Dirgantara; Rahmawati, Desi; Fanisyah, Elsah (Universitas Pendidikan Ganesha, 2023)
Technology is a basic need of everyone so it can be said that educational innovation and educational technology are inseparable whole and causes the use of technology in the scope of education to be a must to achieve a more advanced and quality education. Therefore, it is important to know the development of technology in the scope of education so that it can be the basis for technological development in education in the future. The purpose of this study is to analyze and find out the trends of technology research in the field of education in the last 5 years starting from 2018 to 2022. This study uses bibliometric analysis which is a quantitative statistical analysis tool that is often used to provide analysis of existing publications with the help of VOSviewer to visualize data and use databases in Scopus. Then, based on the results of the analysis, 547 publications were obtained in the span of 5 years, starting from 2018 to 2022, furthermore, technological research trends in education related to publication growth and leading affiliations, leading country and subject area, the most source title, the most cited source, the most cited authors, and keywords co occurances analysis. In addition, this research contributes and also opens up opportunities for future researchers to be able to conduct research related to technology in education, which is still small in the density visualization area.